Perlindungan Hukum Terhadap Perempuan Korban Human Trafficking Sebagai Wujud Perlindungan Hak Asasi Manusia - Elvina Melinda; Joko Setiyono (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
Human Trafficking violates human rights relating to the right to personal liberty. Many of these crimes occurred to vulnerable groups, one of which was women. Therefore, this paper aims first, to know the protection of women’s human rights and legal policies to overcome the criminal act of trafficking women. Second, knowing the responsibility and role of the state towards women trafficking victims. This study uses a normative juridical research method. The results of the discussion show that the protection of women’s human rights has been carried out even though it is still not optimal, so there are several legal policies to overcome it. Apart from that, the responsibility and role of the state towards victims of human trafficking can be seen in the establishment of the Integrated Service Center for the Empowerment of Women and Children and the programs implemented. Thus, it is advisable to carry out counseling in coordination with various related parties, have representatives of the Integrated Service Center for the Empowerment of Women and Children up to the sub-district level, and coordinate in matters of overseas licensing on the grounds of working.